Granny, will your dog bite, and other mountain rhymes - Milnes, Gerald; Root, Kimberly Bulcken (New York : Knopf, 1990)
A collection of rhymes about various aspects of mountain life.
Includes index.
Kirkus Reviews
K-3
Keywords: Mountain life -- Juvenile poetry; Children's poetry, American; Mountain life -- Poetry; American poetry; Mountain life -- Poetry; American poetry